Antecedents and Impacts of Digital Customer Experience in Youth E-Commerce Engagement - Zulfahmi Zulfahmi; Hubertina Karolina Ngarbingan; Ginta Ginting; Maya Maria (AIBPM Publisher, 2026)
To analyze the antecedents and implications of digital customer experience. The proposed research model integrates several theories and approaches, namely 1) Information Integration Theory (IIT), 2) Multi Attribute Theory (MAUT), 3) Value Co-Creation Theory, 4) Theory of flow. From the integration of these theories and concepts, the variables used in the modeling are: online flow, value co-creation, digital customer experience, and customer loyalty. This study involved 182 respondents (young people aged 17 to 45), living in Jakarta and its surrounding cities. Data were processed using Smart-PLS to determine the relationships between variables. The results show that online flow state significantly influences value co-creation, and value co-creation influences digital customer experience. An interesting finding from this research is that digital customer experience and online flow state can be proven to significantly influence customer loyalty. The hypothesis test examines the indirect effect of online flow state on customer loyalty through two consecutive mediators: value co-creation and digital customer experience. The results indicate a significant double mediation effect. To achieve customer loyalty in the context of e-commerce, companies need to strategically create engaging online experiences (trigger flow), encourage active customer participation in value creation, and ultimately, ensure that all of this results in a superior digital customer experience. Based on the research findings, the following recommendations are: a) Prioritize Experience Design that Inspires